Legal Analysis of Corruption Prevention through State Officials’ Asset Declarations - Guruh Tio Ibipurwo (Corruptio, 2025)
Corruption prevention in Indonesia remains weak due to inadequate enforcement of asset disclosure obligations for state officials. Although asset reporting is vital for transparency and accountability, it functions mainly as a formal compliance tool without strong sanctions. Comparative experiences from Denmark and Spain show that effective prevention requires comprehensive legal frameworks combining administrative and criminal penalties to ensure compliance and deter corruption. Indonesia’s current framework, limited to administrative sanctions, lacks coercive power. Strengthening it through explicit legal provisions aligned with international standards such as the UNCAC and OECD guidelines is essential to enhance accountability and reinforce corruption prevention.